Exon-intron organization of the human multidrug-resistance protein 2 (MRP2) gene mutated in Dubin-Johnson syndrome - Tsujii, Hiroyuki; König, Jörg; Rost, Daniel; Keppler, Dietrich (Gastroenterology, 2005)
Background & Aims: The Dubin-Johnson syndrome is characterized by conjugated hyperbilirubinemia and by impaired secretion of anionic conjugates from hepatocytes into bile. Absence of the multidrug-resistance protein 2 (MRP2; symbol ABCC2), an adenosine triphosphate-dependent conjugate export pump, from the hepatocyte canalicular membrane is the molecular basis of this syndrome. The aim of this study was the elucidation of all exon-intron boundaries of the MRP2 gene as a prerequisite for the analysis of mutations in patients with Dubin-Johnson syndrome. Methods: Exon-intron boundaries of MRP2 were determined, and the amplified exons were screened for mutations. Immunofluorescence microscopy served to localize the MRP2 protein in human liver. Results: The human MRP2 gene is ~45 kilobases long; it contains 32 exons and a high proportion of class 0 introns. In 2 patients with Dubin-Johnson syndrome, we detected a nonsense mutation at codon 1066 and a 6-nucleotide deletion mutation affecting codons 1392-1394. The MRP2 protein was absent from the canalicular membrane of both patients. Conclusions: The mutations detected so far show that various mutations in the MRP2 gene can lead to the Dubin-Johnson syndrome. The exon-intron boundaries established in this article will facilitate the analysis of additional mutations in the MRP2 gene. GASTROENTEROLOGY 1999;117:653-660
Available online 27 October 2005
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 23.02.2021